2006
DOI: 10.1111/j.1537-2995.2006.00959.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, controlled Phase III trial of therapeutic plasma exchange with fresh‐frozen plasma (FFP) prepared with amotosalen and ultraviolet A light compared to untreated FFP in thrombotic thrombocytopenic purpura

Abstract: The comparable results between treatment groups observed from this small trial suggest that TPE with PCT FFP was safe and effective for treatment of TTP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 43 publications
4
75
0
2
Order By: Relevance
“…The activity remained low and the inhibitor persisted at early relapse. The improvement of ADAMTS-13 activity or resolution of the inhibitor may not be predictive of remission of idiopathic TTP [22].…”
Section: Discussionmentioning
confidence: 99%
“…The activity remained low and the inhibitor persisted at early relapse. The improvement of ADAMTS-13 activity or resolution of the inhibitor may not be predictive of remission of idiopathic TTP [22].…”
Section: Discussionmentioning
confidence: 99%
“…This uses photochemical treatment, binding DNA and RNA, inactivating viruses, bacteria and leucocytes. It retains critical levels of coagulation proteins and ADAMTS 13 [16] and in a randomised phase III controlled trial, it has been shown to be equally efficacious and safe to standard FFP in acute TTP [17].…”
mentioning
confidence: 99%
“…The 3 phase III clinical studies covered the treatment of congenital coagulopathies, acquired coagulopathies, as well as therapeutic plasma exchange for thrombotic thrombocytopenic purpura (TTP). These studies have demonstrated that the INTERCEPT treated plasma units are comparable to the conventional plasma units in terms of safety and efficacy in the support of the patients [20][21][22].…”
Section: Clinical Experiencementioning
confidence: 90%